Synergizing Science and Spirituality: Crafting an Integrated Curriculum to Elevate Spiritual Intelligence in Madrasah Education - Ahmad Rifai; Umar Manshur; Sayuri Sayuri (Nurul Jadid University, 2023)
This research aims to analyze and understand education in the modern era, which increasingly recognizes the importance of developing aspects of spiritual intelligence as an integral part of forming balanced and ethical individuals and initiating an innovative approach to integrating the spiritual dimension into the educational process in Madrasah. This research was conducted through a qualitative approach to the type of case study. This research was conducted at madrasa institutions Aliyah Nurul Istifadah Based on the results of the research conducted shows that this curriculum development model encourages a holistic educational approach that does not only focus on academic achievement but also on the development of student's character and spiritual intelligence, among others, which are highlighted emphasize values such as; (1) integrity, (2) empathy, (3) sincerity, and (4) gratitude. These values form the basis of a strong character and encourage students to play an active role in society. This will help students understand the meaning of life, social responsibility, and relationships with others.